Bacteroides fragilis participates in the therapeutic effect of methotrexate on arthritis through metabolite regulation - Zhou, Bailing; Dong, Chunyan; Zhao, Binyan; Lin, Ke; Tian, Yaomei; Zhang, Rui; Zhu, Lixin; Xu, Hueng; Yang, Li (Frontiers in Microbiology, 2022)
Methotrexate (MTX) is a preferred disease-modifying anti-rheumatic drug in the management of rheumatoid arthritis (RA). However, the toxicity and inefficiency of MTX limit its clinical application. Gut microbiota has been implicated in the side effects and efficacy of MTX. In this study, the analysis of the gut microbiota in RA patients revealed that the abundances of intestinal B.fragilis was reduced after MTX treatment. We observed that MTX has no obvious therapeutic effect in the absence of B.fragilis, while transplantation of B.fragilis restored the efficacy of MTX in antibiotics-pretreated collagen-induced arthritis (CIA) mice. In addition, B.fragilis gavage was accompanied by an increase in butyrate. Supplementation of butyrate restored the response to MTX in gut microbiota-deficient mice, to a similar level achieved by B.fragilis gavage. These results show that gut microbiota-regulated butyrate plays an essential role in the efficacy of MTX, which will provide new strategies to improve the effectiveness of methotrexate in RA treatment.